Determination of total organic carbon on hybrid organic-inorganic mesoporous silica by FT-NIR spectroscopy. Issue 23 (15th February 2016) - Oliverio, M.; Bonacci, S.; Nardi, M.; Procopio, A.
Abstract : FT-NIR spectroscopy supported by PLS analysis was used as alternative to thermo-analytical techniques in prediction the organic loading of hybrid silica. Abstract : The potential of Fourier transform near-infrared reflectance spectroscopy (FT-NIRS) to predict the organic loading on hybrid organic–inorganic mesoporous silica was studied. Fourty nine samples of MCM-41 functionalized silica were used to build and cross-calibrate a partial least squares (PLS) model, based on the comparison between NIR spectra and thermoanalytical total organic carbon (TOC) measurement. The model was externally calibrated with fifteen reference samples and the error of prediction was determined. The method was robust and stable for samples characterized by a similarity in the organic functional group. FT-NIRS represents a valid, non-destructive analytical technique employable in the synthesis of hybrid silica samples as an alternative to classical thermoanalytical methods for measurement of organic loading.